The let them theory : a life-changing tool that millions of people can't stop talking about / Mel Robbins. - Robbins, Mel, 1968- (Hay House, 2024)
Mel Robbins will teach you that you only need one month to reset on your life, confidence, and motivation and achieve unimaginable breakthroughs.